Prolonged grief disorder in ICD-11 and DSM-5-TR: differences in prevalence and diagnostic criteria - Treml, Julia; Linde, Katja; Brähler, Elmar; Kersting, Anette (Frontiers in Psychiatry, 2024)
Background Prolonged grief disorder (PGD) was recently included as a disorder in the ICD-11 and DSM-5-TR. Although both classification systems use the same name, the criteria content, and diagnostic approach vary. This study aimed to estimate the respective prevalence of PGDICD-11 and PGDDSM-5-TR and examine the diagnostic agreement while varying the diagnostic algorithm of PGDICD-11 (bereavement vs. symptom period; varying number of accessory symptoms). Methods A representative sample of the German general population (N = 2,509) was investigated, of which n=1,071 reported the loss of a close person. PGD symptoms were assessed with the Traumatic Grief Inventory - Self Report Plus (TGI-SR+). Results The point prevalence of PGD among the bereaved varied between 4.7%-6.8%, depending on the criteria and diagnostic algorithm. The prevalence of PGDDSM-5-TR was significantly lower than the prevalence of PGDICD-11. The diagnostic agreement between both criteria sets was substantial and increased after the number of accessory symptoms for PGDICD-11 was increased from one to three. The most common symptoms were intrusive thoughts/images related to the deceased person, longing for the deceased person, and difficulty accepting the loss. Conclusion The results demonstrate that the prevalence of PGD significantly varies depending on the application of the diagnostic algorithm and criteria. PGD affects a substantial proportion of the general population and should be addressed by healthcare providers. However, applying the minimum ICD-11 criteria could lead overestimating the prevalence. Therefore, further harmonizing the ICD-11 and DSM-5-TR criteria and diagnostic algorithm for PGD seems appropriate.